The Relationship of Optimistic Bias with Hygiene and Sanitation Attitudes among Food Handlers in the Canteens of State High School in Magelang City, Indonesia - Khoirunisa', Ayu; Budiningsari, Dwi; Prianto, Joko (BKM Public Health and Community Medicine, 2024)
Purpose: This study examines the relationship between characteristics (age, education, experience, information); optimistic bias; and hygiene sanitation attitudes among food handlers in the canteens of five State High Schools in Magelang City, Indonesia. Method: This research used a quantitative method with analytical observational using the cross-sectional approach. This research involved 41 food handlers in the canteens of five State High Schools in Magelang City, Indonesia, who were selected through total sampling. The independent variable in this research was optimistic bias, while the dependent variable in this research was hygiene and sanitation attitudes. Data were collected using validated questionnaires on optimistic bias and hygiene sanitation attitudes. Optimistic bias was categorized as low optimistic bias (score >24), possible bias (score = 24), and high optimistic bias (score <24). Hygiene sanitation attitudes was categorized as positive attitudes (score ≥50%) and negative attitudes (score <50%). Statistical analysis used the Spearman correlation test. Results: All participants (100%) displayed a high optimistic bias and the vast majority (95.1%) showed a positive attitude toward hygiene and sanitation. There was a significant relationship (p = 0.043 ; r = -0.317) between age and optimistic bias. However, there was no significant relationship between characteristics, optimistic bias, and hygiene sanitation attitudes among food handlers in the canteens of State High School in Magelang City, Indonesia. Conclusion: There is a significant relationship between age and optimistic bias. However, there is no significant correlation between characteristics, optimistic bias, and hygiene sanitation attitudes. Therefore, other stimuli such as facility, environment, and culture are needed to improve the quality of food handler’s attitudes regardless of their optimistic bias.